Analisis Kesulitan Menulis Permulaan Dalam Pembelajaran Bahasa Indonesia Kelas II SDN Kepek Tahun Pelajaran 2023/2024 - Febriyanti, Indah Dwi; Palupi, Yulia (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Palangka Raya, 2024)
This study aims to identify and analyze the difficulties faced by grade II students of SDN Kepek in writing beginning in learning Indonesian Language, and to find out the factors that affect students' ability to write beginning writing. The formulation of this research problem is what the difficulty of writing the beginning is like and what factors affect the difficulty of writing the beginning of grade II students in learning Indonesian Language at SDN Kepek. This study uses a descriptive qualitative approach. Research site of SDN Kedek, Pengasih District, Kulon Progo Regency. The instruments used by the researcher are observation, interviews, and documentation with the research subjects of class II students, and the researcher's informant as a supporting resource person, namely the class II homeroom teacher. The data analysis and interpretation technique uses 3 stages, namely data reduction, data presentation and conclusion drawn. Based on the results of the research, some of the writing difficulties experienced by grade II students through their writing include: letter shapes are difficult to recognize, difficulty adjusting the height of letters, slow writing, no spaces in writing and unclear or illegible writing. Then the factors that cause difficulties in learning to write early are internal factors including weak fine motor skills, weak memory skills, and low interest in learning. Meanwhile, external factors include a lack of parental attention, a less supportive home atmosphere, the learning process at school, and the influence of technology.